Distinct clinical outcomes based on multiple serum cytokine and chemokine profiles rather than autoantibody profiles and ultrasound findings in rheumatoid arthritis: a prospective ultrasound cohort study - Yukitaka Ueki; Tom W J Huizinga; René E M Toes; Shoichi Fukui; Tomoki Origuchi; Takahiro Maeda; Atsushi Kawakami; Tomohiro Koga; Naoki Matsuoka; Toshihiko Hidaka; Naoki Iwamoto; Mami Tamai; et al. (RMD Open)
Objectives To evaluate the potential of clinical factors, ultrasound findings, serum autoantibodies, and serum cytokine and chemokine profiles as predictors of clinical outcomes in rheumatoid arthritis (RA).Patients and methods We included 200 patients with RA treated with biological and targeted synthetic disease-modifying antirheumatic drugs in a prospective multicentre ultrasound cohort study. Their serum levels of multiple cytokines and chemokines, rheumatoid factors, and serum autoantibodies (anti-cyclic citrullinated peptide-2 (anti-CCP2) and anti-carbamylated protein antibodies) were measured at baseline, 3 months and 12 months.Results Dimensionality reduction using 38 cytokines and chemokines demonstrated four distinct clusters that differed significantly regarding the frequencies of remission defined by clinical composite measures and ultrasound evaluations. Prominent differences in IL-1β, IL-5, IL-7, IL-10, IFNγ, GRO, IP-10, MCP-1 and MIP-1β characterised the between-cluster differences. Two distinct groups made of four clusters showed a significant difference in IgM-anti-CCP2 positivity. The least absolute shrinkage and selection operator regression of 38 cytokines and chemokines for Clinical Disease Activity Index (CDAI) remission at 12 months resulted in the selection of MIP-1β. Logistic regression using baseline levels of anti-citrullinated protein antibody, IgM-anti-CCP2 positivity, the CDAI, the total power Doppler score, the cluster by cytokines and chemokines, MIP-1β, methotrexate dose and mechanisms of action revealed that cluster by cytokines and chemokines was the sole significant factor for CDAI remission at 12 months.Conclusions Specific patterns of cytokines and chemokines—no other clinical factors and autoantibody profiles—were important to distinguish patients with RA achieving remission at 12 months.Trial registration number UMIN000012524.